Effect of plant height on control of multiple herbicide-resistant Palmer amaranth (Amaranthus palmeri) in glufosinate/glyphosate-resistant corn - Kaur, Ramandeep; Chahal, Parminder S.; Shi, Yeyin; Lawrence, Nevin C.; Knezevic, Stevan Z.; Jhala, Amit J. (Frontiers in Agronomy, 2023)
Multiple herbicide-resistant (MHR) Palmer amaranth is a troublesome weed in several crops across the USA, including corn. Due to unavoidable weather conditions, it is sometimes not possible for growers to apply pre-emergence herbicide; therefore, post-emergence (POST) herbicide is needed for effective control of MHR Palmer amaranth. The objectives of this study were to evaluate the effect of POST herbicides applied at two heights (10-15 cm and 20-30 cm) for MHR Palmer amaranth control and their effect on Palmer amaranth biomass, density, and seed production as well as yield of glufosinate/glyphosate-resistant corn. Field experiments were conducted at a grower's field near Carleton, Nebraska, USA in 2020 and 2021. Control of MHR Palmer amaranth was affected by the plant height when herbicides were applied. Glufosinate, dicamba, dicamba/diflufenzopyr, and dicamba/tembotrione applied to 10-15 cm tall Palmer amaranth provided ≥ 94% control 30 d after EPOST (DAEPOST), whereas atrazine/bicyclopyone/mesotrione/S-metolachlor applied to 20-30 cm tall MHR Palmer amaranth provided 85% control in 2021. Glufosinate provided 85% to 90% control when applied to 20-30 cm tall Palmer amaranth in both years. At 90 DALPOST, dicamba, dicamba/diflufenzopyr, and dicamba/tembotrione applied to 10-15 cm tall Palmer amaranth provided ≥ 88% control. Dicamba/tembotrione, atrazine/bicyclopyone/mesotrione/S-metolachlor, and dicamba applied to 20-30 cm tall Palmer amaranth provided 85% to 92% control. Glufosinate, dicamba, and atrazine/bicyclopyone/mesotrione/S-metolachlor were the most effective for reducing Palmer amaranth density 2 to 19 plants m −2 when applied to 10-15 cm Palmer amaranth 30 DAEPOST compared with the nontreated control (137 plants m −2 ) in 2021; however, when applied to 20-30 cm Palmer amaranth, glufosinate, and atrazine/bicyclopyone/mesotrione/S-metolachlor reduced density 5 to 19 plants m −2 . At 30 DAEPOST, glufosinate and atrazine/bicyclopyone/mesotrione/S-metolachlor had the lowest Palmer amaranth biomass (3-17 g m −2 ). Corn yield in 2020 was higher than 2021 due to more rain in 2020. All herbicides resulted in a similar yield in 2020. Lower seed production of 6,269 and 1,953 seeds plant -1 for 10-15 cm and 20-30 cm MHR Palmer amaranth were recorded with dicamba and atrazine/bicyclopyone/mesotrione/S-metolachlor.